RETINOBLASTOMA: DETEKSI DINI HINGGA TATALAKSANA TERKINI - Septa Maulana Satya Pratama; Monalisa Nasrul (Yayasan Pendidikan Medika Indonesia, 2023)
Retinoblastoma (RB) is a malignant tumor of the eye. This type of tumor has a fairly high incidence rate in the world and is dominated by children under 5 years. Until now, theories regarding the etiology and pathogenesis of RB are still developing. Even so, RB can still be enforced based on the results of anamnesis, physical examination, and supporting examinations. There are several modalities that can be chosen to treat RB including focal therapy, chemotherapy, radiotherapy, surgery to the latest including Selective Intra Arterial Chemotherapy (SIAC), Intravitreal Chemotherapy, Stereotactic conformal radiotherapy (SCR), Pars plana vitrectomy (VPP) and endoresection. RB has a prognosis that depends on the speed of diagnosis and the accuracy of the therapy given.